A Strange Term in the Homogenization of Parabolic Equations with Two Spatial and Two Temporal Scales. (2nd February 2012) - Flodén, L.; Holmbom, A.; Lindberg, M. Olsson
Abstract : We study the homogenization of a parabolic equation with oscillations in both space and time in the coefficient a ( x / ε, t / ε 2 ) in the elliptic part and spatial oscillations in the coefficient ρ ( x / ε ) that is multiplied with the time derivative ∂ t u ε . We obtain a strange term in the local problem. This phenomenon appears as a consequence of the combination of the spatial oscillation in ρ ( x / ε ) and the temporal oscillation in a ( x / ε, t / ε 2 ) and disappears if either of these oscillations is removed.